A critical review of sociological dialogue between China and the West. (June 2016) - Lin, Zeng; Palmer, James C.
This paper promotes sociological dialogue between China and the West in the wake of China's recent economic growth. The roots of this dialogue in the history of relations between China and the West, as well as in the history of sociology as an academic discipline, are discussed. So too are new developments, such as the communication revolution, which not only enhance opportunities for sociological dialogue but also contribute to the urgent need for dialogue as world tensions escalate. Sociological dialogue, because of its grounding in the methods and systemic focus of sociology as a discipline, has a great potential to be a positive force in increasing international understanding.